1999
DOI: 10.1123/pes.11.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influence on Children’s Cognitive and Affective Responses to Competitive Soccer Participation

Abstract: This study examined the relationship between children’s perceptions of parental influence and their psychosocial responses to competitive soccer participation. Female (n = 114) and male (n = 113) athletes completed self-reports of soccer competence, enjoyment, intrinsic motivation, and parents’ influence on their participation. Mothers (n = 160) and fathers (n = 123) reported their own attitudes and behaviors toward their child’s participation. Regression analyses revealed that mothers and fathers who were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
1
19

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(184 citation statements)
references
References 28 publications
10
146
1
19
Order By: Relevance
“…These players are more sensitive to parental presence, as indicated by hypothesis 1,19 which is more unusual for them than for tennis players. We speculate that this 20 activity effect supersedes the gender differences in personality that are usually used 21 to explain differences between male and female tennis players.…”
Section: Parenting Practices Variations Across Gender Sport and Perfmentioning
confidence: 94%
“…These players are more sensitive to parental presence, as indicated by hypothesis 1,19 which is more unusual for them than for tennis players. We speculate that this 20 activity effect supersedes the gender differences in personality that are usually used 21 to explain differences between male and female tennis players.…”
Section: Parenting Practices Variations Across Gender Sport and Perfmentioning
confidence: 94%
“…Finally, regarding competence, participants discussed the importance of parents who focus on children's strengths and encourage children to take on sport challenges. Likewise, Babkes and Weiss [54] demonstrated that children whose parents had more positive beliefs about their soccer competency had higher self-perceptions of competence.…”
Section: Positive Sport Parent Behaviourmentioning
confidence: 99%
“…8, No. 3;& Weiss, 1999Scanlan & Lewthwaite, 1986;Scanlan et al, 1993). The participants responded on a five-point Likert scale from "not at all" (1) to "very much" (5).…”
Section: Enjoyment In Swimmingmentioning
confidence: 99%